160 DILEMA KEBIJAKAN YANG PRO RAKYAT (Peraturan Gubernur Kalimantan Tengah No 15 Tahun 2010 tentang Pembukaan Lahan dan Pekarangan Bagi Masyarakat) - Djumaty, Brian L; Hayam Dey, Nina Putri (Universitas Kristen Satya Wacana, 2017)
Since the enactment of decentralization local government have been granted the authority to organize, protect society etc. Given the authority that Central Kalimantan provincial government issued a policy (Pergub No. 15 tahun 2010 on guidelines for land clearing and yard for the people) to protect the local community in the tradition / habit of farming by burning forests to customary provisions. The aim of this study is to describe and analyze the extent to which public policy relevance since the issuance of the policy in 2010-2015 and to what extent these policies protect the local wisdom. the method used is descriptive qualitative study, using the study of literature in the process of data collection. Results and discussion of these studies show that 1) in 2015 created a policy that is no longer relevant because the whole area of Central Kalimantan is 15.3 million hectares, 12.7 hectares (78%) is controlled by plantation companies. 2) goodwill by the Government of Central Kalimantan to protect local communities need to be given appreciation. But this policy could apply / relevant if it is done before the 90s because many forests and local people still farming to meet food needs.